An Evidence-based Prehospital Guideline for External Hemorrhage Control: American College of Surgeons Committee on Trauma. (3rd April 2014) - Bulger, Eileen M.; Snyder, David; Schoelles, Karen; Gotschall, Cathy; Dawson, Drew; Lang, Eddy; Sanddal, Nels D.; Butler, Frank K.; Fallat, Mary; Taillac, Peter; White, Lynn; Salomone, Jeffrey P.; et al.
Abstract This report describes the development of an evidence-based guideline for external hemorrhage control in the prehospital setting. This project included a systematic review of the literature regarding the use of tourniquets and hemostatic agents for management of life-threatening extremity and junctional hemorrhage. Using the GRADE methodology to define the key clinical questions, an expert panel then reviewed the results of the literature review, established the quality of the evidence and made recommendations for EMS care. A clinical care guideline is proposed for adoption by EMS systems. Key words: tourniquet; hemostatic agents; external hemorrhage